Inference of oxidative stress in patients with hypothyroidism - Rada, Feryal (Publishing Office of the University of Rzeszow, 2024)
Introduction and aim. Oxidative stress is one of the complications that accompany defects in thyroid hormone levels. This study was designed to evaluate oxidative stress markers in patients with hypothyroidism. Material and methods. This case control study was comprised of forty-two hypothyroid patients aged 36–46 years and forty age matched (35–43 years) healthy control participants randomly selected from the Endocrine Clinic of Al-Yarmook Hospital in Iraq. Blood levels of thyroid hormones malondialdehyde, glutathione, and paraoxonase-1 were assessed. Body mass index was calculated for each patient and control participant. Results. Regarding the data of oxidative stress markers in hypothyroid patients compared to controls, a significant elevation was reported in blood levels of malondialdehyde and a significant reduction was found in blood levels of glutathione (p=0.031). On the other hand, the blood levels of paraoxonase-1 were significantly different in hypothyroid patients compared with the control. Conclusion. Elevated blood levels of malondialdehyde and declined blood levels of glutathione in hypothyroid patients are a signal of oxidative stress and consequently increase the risk of cardiovascular complications.
The rules of this study followed the Helsinki Declaration for research on humans and was approved by the College Ethical Committee of the Pharmacy College (2/4/1236 on 22-11-2021).
Keywords: glutathione; hypothyroidism; malondialdehyde; oxidative stress; paraoxonase-1